Potential use of histone deacetylase inhibitors in cancer therapy - Gołąbek, Karolina; Strzelczyk, Joanna K.; Wiczkowski, Andrzej; Michalski, Marek (Contemporary Oncology/Współczesna Onkologia, 2015)
Epigenetics is a branch of science that focuses on mechanisms related to control and modification of expression of genetic material without any changes to its sequences. Such mechanisms include post-translational modifications of histones. It is widely known that carcinogenesis is related to hypoacetylation of genes that influence apoptosis, the cell cycle, cell signaling, the immunologic response, angiogenesis and occurrence of metastasis. Currently conducted research focuses on several strategies related to epigenetic therapy. One such strategy is based on the use of histone deacetylase inhibitors. This paper presents mechanisms through which these compounds work and a summary of their characteristics. It also includes a review of clinical tests related to histone deacetylase inhibitors, as well as their relationship with other chemotherapeutic methods. A better understanding of the involved mechanisms will provide a rational basis to improve the therapeutic outcome of available antitumor agents.